(untitled) (Research, Society and Development, 2020)
The aim of the study was to verify vocal, respiratory and self-assessment aspects of a group of teachers without laryngeal affections after intensive therapy with Finger Kazoo vocal technique. This is a case study with five adult male teachers evaluated before and after 15 sessions of intensive brief therapy with Finger Kazoo, with descriptive analysis. After therapy, most of the maximum phonation times increased, being within the normal range; the s/z and ė/e relations remained normal; the difference between the mean of the vowels and the count of numbers, as well as the sound pressure level, remained above normal; the upper limit of the dynamic extension has decreased; there were reductions in amplitude perturbation, noise and fundamental frequency measurements. In the Vocal Tract Discomfort Scale, there was a reduction in the frequency and intensity of sensations and symptoms; but in the Voice-Related Quality of Life Protocol, with the exception of the socioemotional score, and Vocal Handicap Index, there was worsening. It was concluded that in this group of male teachers, after intensive brief therapy with Finger Kazoo, there were positive results in measures of maximum phonation time, fundamental frequency, amplitude perturbation, noise, upper limit of dynamic extension and self-perception of vocal tract discomfort and socioemotional domain of the Voice-Related Quality of Life Protocol.